Background interference on the color of dental composite materials with different thickness by digital contrast - Lins, Emery C.; Florez, Fernando L. E.; Portero, Priscila P.; Lizarelli, Rozane F. Z.; Oliveira Jr., Osmir B.; Bagnato, Vanderlei S. (SPIE, the international society for optics and photonics, 2007)
In this work the color dependence of resin composites with the background color was evaluated. The objective was to measure since what thickness the color of the sample stops being influenced by the color of the background over which the resin is placed and the methodology used in experiment was based in analyzing the contrast of digital images of the sample over a black background. The results shown that since 0.8 mm the images contrast becomes almost constant; it prove that since this thickness the color of resin composite depends on the optical resin properties only. The experiment was repeated under three conditions of luminosity to evaluate the influence of it on the image contrast and the results obtained were identical.
Keywords: Background; Color; Composite materials; Contrast; White-LED; Dental composites; Image processing; Light emitting diodes; Luminance; Resins; Digital contrast; Digital images; Resin composite; Light interference